The Realization of Tenor in the Students’ Argumentative Essays - Ruli, Ruli; Rukmini, Dwi; Widhiyanto, Widhiyanto (Universitas Negeri Semarang, 2021)
Writing an argumentative text requires knowledge to encode the meaning, such as the interpersonal meaning. The interpersonal meaning relates to how the writer realizes tenor in the text. The tenor encodes participants involved in the text, how the relationship between them, and what kind of attitude discovered in the text. Those meanings are covered in the three aspects of tenor: personalization, standing, and stance. This study analyzed the argumentative essays written by the English Education students of Palangkaraya University. It employed a qualitative research approach, and the research objects were argumentative essays. The results revealed that most of the students tended to be objective in conveying their argument. They tried not to involve themselves in taking a position in their essays. Unfortunately, they did not try to increase their authority by supporting their opinion with the sources. It was caused by the limitation of time and the prohibition of using handphones during writing. Even so, they shared their experiences to strengthen their argument. Besides, the students conveyed the attitude openly, even though some students wanted to be neutral. It can be implied that it is essential for the students to be more careful in selecting and applying particular language features of tenor in English writing.